Satisfaction with medication in older adult patients with chronic respiratory diseases: a multicenter cross-sectional observational study - Wu, Jiankang; Meng, Weiwei; Zeng, Huihui; Ma, Yiming; Chen, Yan (Frontiers in Public Health, 2023)
Purpose To gain insight into medication satisfaction and factors associated with chronic respiratory disease, particularly chronic obstructive pulmonary disease (COPD) in older adults, focusing on public health issues and improving the health of the older adult population. Methods This cross-sectional study was conducted from October 2022 to November 2022 in 24 hospitals in different regions of Hunan Province, China. Older adult patient treatment satisfaction was assessed using the Treatment Satisfaction Questionnaire for Medication version II. Multiple regression analysis was used to identify factors independently associated with patient treatment satisfaction. Results Only 15.9% of all patients scored above 80 in the effectiveness domain, while 11.6 and 16.5% scored above 80 in the convenience and global satisfaction domains, respectively, while 17.3% reported having side effects. Interstitial lung disease was associated with lower drug satisfaction than other disorders (p < 0.05). Multifactorial regression analysis showed that age, education background, profession, and smoking status were independently associated with satisfaction among patients with chronic respiratory diseases (p < 0.05). Education background, profession, CAT score, number of acute exacerbations, duration of home oxygenation and duration of home ventilator use were independently associated with satisfaction in patients with COPD (p < 0.05). Conclusion Low satisfaction with chronic respiratory drug therapy was associated with age, education background, profession and smoking status. Satisfaction was lower for patients with interstitial lung disease. For COPD, CAT score, education background, profession, number of acute exacerbations, home oxygen and ventilator use influence satisfaction. Clinicians can identify appropriate patients and communicate effectively with them throughout treatment and follow-up, vigorously promote smoking cessation and home oxygen therapy, increase medication satisfaction, especially among older adults, and in turn improve public health and the quality of life of older adults.